The Emerging Roles of Human Leukocyte Antigen-F in Immune Modulation and Viral Infection - Lin, Aifen; Yan, Wei-Hua (Frontiers in Immunology, 2019)
Human leukocyte antigens (HLAs) play various critical roles in both innate and adaptive immunity through processes such as presenting antigens to T cells and serving as ligands for receptors expressed on NK cells. Among the HLA class I family, the clinical significance and biological function of HLA-F have been the least investigated and have remained elusive for a long period of time. Previous studies have revealed that HLA-F expression might be involved in various physiological and pathological processes, such as pregnancy, viral infection, cancer, transplantation and autoimmune diseases. However, recent data have shown that, akin to other HLA family members, HLA-F molecules can interact with both activating and inhibitory receptors on immune cells, such as NK cells, and can present a diverse panel of peptides. These important findings pave new avenues for investigations regarding the functions of HLA-F as an important immune regulatory molecule. In the present review, we summarize the studies on the role of HLA-F in immune modulation, with a special emphasis placed on the roles of HLA-F and KIR3DS1 interactions in viral infection.